The Journey Towards Empowerment of Former Youth Scholars of Gems Heart Outreach Development Inc: A Phenomenological Study - Dicen, Joven (International Journal of Sustainability and Advanced Integrated Research, 2026)
This phenomenological study explored the journey toward empowerment of former youth scholars of Gems Heart Outreach Development, Inc. (GHODI). It aimed to describe and reflectively analyze the lived experiences of former youth scholars, identify the significant meanings and insights derived from their experiences, and determine the implications of these insights in the field of Social Work. The study was anchored on phenomenological inquiry and related perspectives on empowerment, poverty, and community development. A qualitative phenomenological research design was employed to provide an in-depth understanding of the participants lived experiences. The study involved four (4) former youth scholars of GHODI who shared their narratives through the research process. The findings revealed that the participants experienced challenges related to economic limitations, educational struggles, and difficult life situations that affected their pursuit of education. Despite these challenges, the support provided through the scholarship program, together with encouragement from family and other support systems, contributed to the development of motivation, confidence, leadership skills, and personal transformation. The experiences of the participants demonstrated that educational assistance and community-based interventions can help individuals overcome barriers and become self-sustaining and empowered individuals. The study highlighted the significant roles of parents, social support networks, and organizations in fostering growth, engagement, and empowerment among youth scholars. The study is aligned with Sustainable Development Goal 4 (Quality Education), which promotes inclusive and equitable education and lifelong learning opportunities, as the research emphasizes the role of educational assistance in improving opportunities for underprivileged youth. The sustainability impact of the study lies in strengthening community-based educational support initiatives that contribute to individual development, social empowerment, and the reduction of barriers associated with poverty and limited access to education. The study recommends sustaining programs that provide educational opportunities, encouragement, and support mechanisms for disadvantaged youth and communities.